Intercalary fragments in posterior malleolar fractures: incidence, treatment implications, and distribution within CT-based classification systems - Mueller, Elena; Kleinertz, Holger; Tessarzyk, Marlon; Rammelt, Stefan; Bartoníček, Jan; Frosch, Karl-Heinz; Barg, Alexej; Schlickewei, Carsten (European journal of trauma and emergency surgery, 2023)
INTRODUCTION: Complex ankle fractures frequently include the posterior malleolus (PM). Despite advances in diagnostic and treatment strategies, PM fracture involvement still predisposes to worse outcomes. While not incorporated into the most common PM fracture classifications, the presence of an intercalary fragment (ICF) complicates treatment. This study aims to describe the incidence, morphology, and location of ICFs in PM fractures. MATERIALS AND METHODS: A total of 135 patients with a mean age of 54.4 (SD ± 18.9) years and PM fractures were analyzed for the presence of an ICF. Patients with an ICF were compared to those without in terms of age, gender, and treatment received. Characteristics of the ICFs in terms of location and size were assessed. Furthermore, the presence of an ICF in relation to the PM fracture classification according to Haraguchi et al., Bartoníček/Rammelt et al., and Mason et al. was investigated. RESULTS: ICFs presented in 55 (41%) of the 135 patients. Patients with an ICF were younger, and the PM was more often operatively treated when compared to patients without an ICF. A posterolateral approach was used significantly more often in patients with an ICF. Almost all ICFs were found in the posterolateral (58%) and posterocentral (35%) regions. The majority of fragments were found in Bartoníček/Rammelt type 2 fractures, the most common fracture type. Bartoníček/Rammelt type 3 fractures had the highest relative frequency of ICFs. CONCLUSION: ICFs are frequently found in PM fractures; however, they are not incorporated into any of the common classifications. They are generally found in younger patients and associated with more complex PM fractures. As they can complicate reduction of the main fragment and may require direct exposure to restore joint congruency, ICFs should be considered in PM fracture classifications. Due to their location, the majority of ICFs are able to be accessed using a posterolateral approach.
Keywords: Ankle Fractures; výsledek terapie; Tomography, X-Ray Computed; Bartoníček/Rammelt; lidé; Tibia; Intercalary fragment; Treatment Outcome; Ankle fracture; Incidence; retrospektivní studie; incidence; Posterior malleolar fracture; tibie; počítačová rentgenová tomografie; vnitřní fixace fraktury; lidé středního věku; Retrospective Studies; Middle Aged; Fracture Fixation, Internal; fraktury kotníku; Humans